Imagining Iberia in English and Castilian Medieval Romance - Houlik-Ritchey, Emily (University of Michigan Press, 2023)
Imagining Iberia in English and Castilian Medieval Romance offers a broad disciplinary, linguistic, and national focus by analyzing the literary depiction of Iberia in two European vernaculars that have rarely been studied together. Emily Houlik-Ritchey employs an innovative comparative methodology that integrates the understudied Castilian literary tradition with English literature. Intentionally departing from the standard "influence and transmission" approach, Imagining Iberia challenges that standard discourse with modes drawn from Neighbor Theory to reveal and navigate the relationships among three selected medieval romance traditions. This welcome volume uncovers an overemphasis in prior scholarship on the relevance of "crusading" agendas in medieval romance, and highlights the shared investments of Christians and Muslims in Iberia's political, creedal, cultural, and mercantile networks in the Mediterranean world.